2016
DOI: 10.1186/s13017-016-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and predictors of mortality in necrotizing fasciitis patients in a single tertiary hospital

Abstract: BackgroundNecrotizing fasciitis (NF) is a fatal aggressive infectious disease. We aimed to assess the major contributing factors of mortality in NF patients.MethodsA retrospective study was conducted at a single surgical intensive care unit between 2000 and 2013. Patients were categorized into 2 groups based on their in-hospital outcome (survivors versus non-survivors).ResultsDuring a14-year period, 331 NF patients were admitted with a mean age of 50.8 ± 15.4 years and 74 % of them were males Non-survivors (26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
102
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 44 publications
(54 reference statements)
13
102
5
Order By: Relevance
“…The demographics of our cohort display the same trends as have been described in other studies (Table ). NSTI patients, both survivors and non‐survivors, were older than abscess patients (p‐value 0.029 and 0.005, respectively).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The demographics of our cohort display the same trends as have been described in other studies (Table ). NSTI patients, both survivors and non‐survivors, were older than abscess patients (p‐value 0.029 and 0.005, respectively).…”
Section: Resultssupporting
confidence: 60%
“…There have been numerous reports on the microbiology of NSTIs , but they have almost always used data obtained by traditional culture methods. Furthermore, many institutions report culture‐negative results in a rapidly progressive wound bed , further illustrating the restraints of culture‐based diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Although Vibrio NF has high mortality, our study showed that this had no clinical correlation with mortality in late amputation. Jabbour et al reported that among gram-positive bacteria in NF, Streptococcus and Staphylococcus were the most commonly identified organisms [18]. In our study, V. vulnificus accounted for 34.6%, while Streptococcus species and polymicrobial infection both accounted for 13.2% of cases.…”
Section: Discussionsupporting
confidence: 45%
“…Polybacterial infections were the most frequent among the other groups (33%). The latter is expected because NF is, by definition, a form of deep tissue infection whereas PG is a reactive, non‐infectious unlike that reported the literature, in our study cohort, we identified Pseudomonas as a predominant gram‐negative microorganism and Enterobacter as a gram‐positive microorganism …”
Section: Discussionmentioning
confidence: 47%
“…First introduced by Wilson in 1952 as a more accurate description, necrotising fasciitis (NF) is an uncommon condition with an incidence rate of 4 to 13/1 000 000 annually . It is mostly a polymicrobial, severe soft tissue infection that progresses rapidly, penetrating through the subcutaneous tissue to the fascial planes and the muscles.…”
Section: Introductionmentioning
confidence: 99%